Synergistic effects of mica and wollastonite fillers on thermal performance of intumescent fire retardant coating - Zia-ul-Mustafa, M. (American Institute of Physics Inc., 2015)
In this study, intumescent fire retardant coatings (IFRC) were developed to investigate the synergistic effects of reinforced mica and wollastonite fillers based IFRC towards heat shielding, char expansion, char composition and char morphology. Ammonium poly-phosphate (APP) was used as acid source, expandable graphite (EG) as carbon source, melamine as blowing agent, boric acid as additive and Hardener H-2310 polyamide amine in bisphenol A epoxy resin BE-188(BPA) was used as curing agent. Bunsen burner fire test was used for thermal performance according to UL-94 for 1 h. Field Emission Scanning Electron Microscopy (FESEM) was used to observe char microstructure. X-Ray Diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR) were used to analyse char composition. The results showed that addition of clay filler in IFRC enhanced the fire protection performance of intumescent coating. X-Ray Diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR) results showed the presence of boron phosphate, silicon phosphate oxide, aluminium borate in the char that improved the thermal performance of intumescent fire retardant coating (IFRC). Resultantly, the presence of these developed compounds enhanced the Integrity of structural steel upto 500Â°C. Â© 2015 AIP Publishing LLC.